Analisa Desain Kemasan Stik Sukun (Artocarpus Altili) Menggunakan Metode Value Engineering - Anisha Dian Iswahyuni (Jurnal Teknik, 2020)
The packaging design of a product is a special attraction for consumers. The right design would be able to increase sales of a product. The purpose of this research is to get the best packaging by designing or creating a packaging concept according to the needs and desires of consumers based on the packaging analysis used. The packaging development method is carried out with a product development approach and value engineering by improving performance based on consumer desires using the FAST method (Function Analysis System Technique). Based on the results of the identification of consumer needs, the testing phase, and the selection of alternative packaging development concepts to the concept analysis, the final product for the selected breadfruit stick packaging is a custom packaging printing made of solid aluminum foil pouch, with the custom size of 14x23cm, printed sticker, full printed design, net size 100-200 grams, packaging basic color of gold, original flavor variant, the price ranges from Rp. 10,000 to Rp. 20,000, using a seal (sealer) and having PIRT and Halal certification. With the proposed packaging, it is hoped that the sales of breadfruit stick products would be increased.